Enterprise Resource Planning system and its impact on tourism companies' operational performance - Mohamed, Ghada Abdalla; Farahat , Esraa Reda Hassan (Journal of Sustainable Tourism and Entrepreneurship, 2019)
Abstract Purpose: The purpose of this study was to find out the relationship between applying the Enterprise Resource Planning system and operational performance, and to develop proposed framework to achieve the requirements of the ERP system, in addition, to measure its availability within tourism companies. Research methodology: The study design is a qualitative study. Data are presented in descriptive form, with in-depth and adaptable analysis. Sample Collection by intentional sampling, the sample chosen depends on the study objectives without regard to the ability of a generalist. The study was based on the distribution of a survey list on a random sample of employees of tourism companies in Egypt. Results: The structural equation modeling results indicate that all the employed dimensions to gauge the impact of ERP system (represented by the components of the system), have direct influence and an indirect impact on the operational performance and then access to the quality of tourism service provided. These findings help to explain the mixed discoveries in the literature concerning the pattern of the causal relationship between ERPs with operational performance and service quality. Limitation: The field study data were collected from survey forms from May to July 2019. Three hundred thirty questionnaire forms were distributed, 310 usable replies were received with a response rate of 93.9%. Contribution: Enterprise Resource Planning (ERP) system has received considerable attention in the last years. Many organizations seek to integrate their IT infrastructures by implementing the Enterprise Resource Planning system (ERP). So implementing ERP system helps tourism companies in raising performance rates through reducing the time to do more business, reducing cost, increasing productivity, which leads to higher performance rates. Keywords: Enterprise Resource Planning system, ERP business value, ERP benefits, Operational performance